2014
DOI: 10.2527/jas.2012-6065
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of retail beef yield and fat content from live animal and carcass measurements in Nellore cattle1

Abstract: Data from 156 Nellore males were used to develop equations for the prediction of retail beef yield and carcass fat content, expressed as kilograms and as a percentage, from live animal and carcass measurements. Longissimus muscle area and backfat and rump fat thickness were measured by ultrasound up to 5 d before slaughter and fasted live weight was determined 1 d before slaughter. The same traits were obtained after slaughter. The carcass edible portion (CEP in kg and CEP% in percentage; n = 116) was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
1
9
1
Order By: Relevance
“…The addition of ULMA and UFAT variables to the regressions of PHW and RW on live measures did not result in large increases in R 2 but did lead to reduced lack of fit (C p ≈ p) and reduced residual variance. Equations of FQW and PHW with carcass measures as independent variables fit better based on R 2 , C p , and RMSE than equations with live measures as in-found fat depth to be an important predictor of FAT (Perkins et al, 1992;Robinson et al, 1992;Bergen et al, 2005;Sakamoto et al, 2014). The discrepancy between the present study and those conducted previously may be due to the relative leanness of the cattle in this study.…”
Section: Resultscontrasting
confidence: 80%
See 3 more Smart Citations
“…The addition of ULMA and UFAT variables to the regressions of PHW and RW on live measures did not result in large increases in R 2 but did lead to reduced lack of fit (C p ≈ p) and reduced residual variance. Equations of FQW and PHW with carcass measures as independent variables fit better based on R 2 , C p , and RMSE than equations with live measures as in-found fat depth to be an important predictor of FAT (Perkins et al, 1992;Robinson et al, 1992;Bergen et al, 2005;Sakamoto et al, 2014). The discrepancy between the present study and those conducted previously may be due to the relative leanness of the cattle in this study.…”
Section: Resultscontrasting
confidence: 80%
“…This is again expected, as HQRTP is a substantial portion of HCW. Previous studies have found fat depth measured with ultrasound to be an important predictor of HQRTP (Greiner et al, 2003;Tarouco et al, 2007;Silva et al, 2012;Sakamoto et al, 2014). In the present study, a positive relationship was observed between HQRTP and UFAT, demonstrating that the first variable increases as consequence of the increase of the second.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The carcass cuts were divided into hindquarter, forequarter, and spare ribs (Yokoo et al, 2003). Only the left carcass side was used for measurement of the cuts and the records were multiplied by two to obtain the result for the whole carcass (Sakamoto et al, 2014). The hot carcass yield (CY) was calculated using the following equation: CY = hot carcass weight /FLW × 100.…”
Section: Methodsmentioning
confidence: 99%